2019
DOI: 10.3389/fphar.2019.00517
|View full text |Cite
|
Sign up to set email alerts
|

METTL3/m6A/miRNA-873-5p Attenuated Oxidative Stress and Apoptosis in Colistin-Induced Kidney Injury by Modulating Keap1/Nrf2 Pathway

Abstract: Nephrotoxicity of colistin is the major factor limiting its clinical application. However, the exact mechanism of colistin-induced nephrotoxicity is still elusive. N 6 -Methyladenosine (m 6 A) modification has been implicated in many biological processes, however, its role in colistin-induced nephrotoxicity needs to be elucidated. Mouse renal tubular epithelial cells (mRTECs) were treated with 200 μM colistin with or without METTL3 overexpression. Cells injury, m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 50 publications
(79 reference statements)
3
73
0
2
Order By: Relevance
“…The lncRNA ARHGAP5-AS1, miR-600, miRNA let-7g, and miR-33a can influence human cancer progression by targeting METTL3 (35,36,52,53). Conversely, METTL3 can promote pri-miRNA processing by interacting with DGCR8 (2,20,54). Dysregulation of METTL3 in various cancers can also influence cancer cell EMT (23,49,50), apoptosis (36,47), and stem cell self-renewal (38,39), which have been identified to be important in cancer progression.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA ARHGAP5-AS1, miR-600, miRNA let-7g, and miR-33a can influence human cancer progression by targeting METTL3 (35,36,52,53). Conversely, METTL3 can promote pri-miRNA processing by interacting with DGCR8 (2,20,54). Dysregulation of METTL3 in various cancers can also influence cancer cell EMT (23,49,50), apoptosis (36,47), and stem cell self-renewal (38,39), which have been identified to be important in cancer progression.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Han et al found that METTL3 positively modulates pri-miR221/222 processing in an m 6 A-dependent manner by interacting with DGCR8, resulting in a reduction in the PTEN level, which ultimately results in proliferation of bladder cancer (29). Wang et al explored the function and mechanism of METTL3 and m 6 A in colistin-induced kidney injury and found that METTL3 interacts with DGCR8 and positively modulates the processing of mature miR-873-5p in an m 6 A-dependent manner (54). Collectively, this evidence suggests that DGCR8 plays an important role in the m 6 A-dependent regulation of miRNA processing by METTL3.…”
Section: Mettl3 Modulates Mirna Processing Via Dgcr8mentioning
confidence: 99%
“…So far, m 6 A has been found not only in mRNAs, but also in a variety of non-coding RNAs including rRNA, tRNA, snRNA, miRNA, and lncRNA [14,15]. For example, m 6 A methyltransferase-like 3 (METTL3) interacts with the microprocessor protein DGCR8 and modulates miR-873-5p mature process positively [16]. The expression of m 6 A demethylase fat mass and obesity-associated protein (FTO) can influence the steady state level of various miRNAs, including increased expression of hsa-miR-6505-5p, hsa-miR-651-5p and hsa-miR-493-5p, and decreased expression of hsa-miR-7-5p, hsa-miR-92a-1-5p and hsa-miR-6769a-3p [15].…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting was carried out as previously described (Wang et al, 2019). Nuclear proteins were extracted using a Nuclear Protein Extraction Kit (Solarbio, Beijing, China) and total protein were prepared in radio-immunoprecipitation assay (RIPA) lysis buffer containing 0.5 mM PMSF (Beyotime, Haimen, China), and centrifuged at 12,000 × g for 15 min at 4°C.…”
Section: Western Blottingmentioning
confidence: 99%
“…The procedure was carried out as described previously (Wang et al, 2019). Briefly, total RNA was extracted using Trizol reagent (Life Technologies, Grand Island, NY, USA) according to the manufacturer's instructions.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%